Dwa światy, dwa style negocjacji – o kulturowej determinacji w inicjowaniu dyskursu handlowego - KATARZYNA SUJKOWSKA-SOBISZ (Stylistyka, 2019)
The author defines a commercial discourse as a model which can be described thanks to analyzed texts which preceded the sales process between tenderers and texts which are or could be results of the sales. In this study, the author is interested in expressions with which – at least two persons in a direct contact during speaking – try to achieve a common financial and sales goal.